2019
DOI: 10.1007/s40333-019-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Shrub modulates the stoichiometry of moss and soil in desert ecosystems, China

Abstract: Desert mosses, which are important stabilizers in desert ecosystems, are distributed patchily under and between shrubs. Mosses differ from vascular plants in the ways they take up nutrients. Clarifying their distribution with ecological stoichiometry may be useful in explaining their mechanisms of living in different microhabitats. In this study, Syntrichia caninervis, the dominant moss species of moss crusts in the Gurbantunggut Desert, China, was selected to examine the study of stoichiometric characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
1
14
0
Order By: Relevance
“…In the current study, no signi cant differences in moss C content were found in different spatial scales, except that moss C in below-ground parts. In addition, our previous studies found that moss C did not shift with changes of moss patch size and microhabitats (Li et al, 2019a;Li et al, 2019b). Thus, our previous and current results suggested that moss C was stable in different spatial scales from patch size (cm) to sampling site (10Km).…”
Section: Different Responses Of Mosses and Soil Characteristics To Variable In Spatial Scalesupporting
confidence: 70%
See 1 more Smart Citation
“…In the current study, no signi cant differences in moss C content were found in different spatial scales, except that moss C in below-ground parts. In addition, our previous studies found that moss C did not shift with changes of moss patch size and microhabitats (Li et al, 2019a;Li et al, 2019b). Thus, our previous and current results suggested that moss C was stable in different spatial scales from patch size (cm) to sampling site (10Km).…”
Section: Different Responses Of Mosses and Soil Characteristics To Variable In Spatial Scalesupporting
confidence: 70%
“…However, the ecological stoichiometry was rarely used in moss studies (Ball and Guevara, 2015;Ball and Virginia, 2014). Previous studies have found that moss stoichiometry is easily in uenced by environments (Ball and Guevara, 2015;Li et al, 2019a;Li et al, 2019b), and that moss growth showed consistent Potassium (K) or N-K colimitation in peatleads (Wang et al, 2016). Potassium is an important nutrient element which can enhance plant N retention (Chiwa et al, 2019;Osaki, 1995) and in uence the plant growth and photosynthetic rate in vascular plant (Cuzzuol et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The N:P of H. ammodendronplants and organs in the study area was higher than 16, indicating thatH. ammodendron in the study area was more limited by P than N (Nie et al, 2022;Li et al, 2019). In this study, the N:P in leaves and stems of H. ammodendron was significantly higher than in roots, which may be resulted from the higher utilization efficiency of N and P in aboveground parts (Kerkhoff et al, 2006).…”
Section: H Ammodendronmentioning
confidence: 51%
“…Thus, the increase in available N in crusted soils are indeed more than that in uncrusted soils (Tao et al 2020), leading to the high leaf N concentration of plants in the Gurbantunggut Desert to a large extent. In contrast, although soil available P can also be increased by BSCs to an extent (Li et al 2019), the impact is quite low mainly because of the harsh environment (e.g., dryhot, and alkaline soil) and low amount of phosphorussolubilizing bacteria. Furthermore, soil nutrient heterogeneity did not consistently influence leaf stoichiometry, as evidenced by their nonsignificant correlation coefficients (Table 3).…”
Section: Potential Influencing Factors On Stoichiometry Of Ephemeralsmentioning
confidence: 99%